PENGARUH PAPARAN MEDAN MAGNET EXTREMELY LOW FREQUENCY (ELF) 500 μT TERHADAP DERAJAT KEASAMAN (Ph), MASSA JENIS, DAN KUALITAS FISIK JAMBU AIR - Rosdiana Afifah Rahman; Sudarti Sudarti (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
One of the plants that can thrive in Indonesia is guava. Indonesian people are familiar with water guava, and the fruit is often consumed by the public. However, water guava will rot quickly if not stored properly. Therefore, we need a method to preserve water guava without reducing the content contained in it. This article aims to analyze the effect of exposure to the ELF magnetic field on pH, density, and physical quality of water guava. The method used in this research is a laboratory experiment with a completely randomized design. This study used a magnetic field exposure of 500 T. The duration of exposure is divided into three, namely 60 minutes, 90 minutes, and 120 minutes. This study was conducted for 4 days with the variables measured in this study namely pH, density, and physical quality of water guava. Measurement of each variable was carried out every day for 4 days.